2019
DOI: 10.1039/c9ta04640b
|View full text |Cite
|
Sign up to set email alerts
|

Simple and scalable synthesis of CuS as an ultrafast and long-cycling anode for sodium ion batteries

Abstract: Simple and scalable synthesis of binder free CuS anode with ultrafast, high capacity and long-cycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 79 publications
1
33
0
Order By: Relevance
“…[33][34][35] In addition, Park et al found that Cu 1.8 S shows an intercalation/deintercalation reaction mechanism without irreversible phase transformation, but most of metal sulfides experience a conversion reaction mechanism, [36] and there are some similar researches to CuS materials for sodium ion storage. [37,38] According to the latest report, nitrogen-doped carbon-coated Cu 9 S 5 bullet-like hollow particles and hierarchical CuS@CoS 2 double-shelled nanoboxes have been prepared by morphology design and nanostructure engineering and both have superior rate capability and long cycle life. [39,40] However, behind the reaction mechanisms there still exist some unclear issues related to the reaction pathways and phase transformation.…”
mentioning
confidence: 99%
“…[33][34][35] In addition, Park et al found that Cu 1.8 S shows an intercalation/deintercalation reaction mechanism without irreversible phase transformation, but most of metal sulfides experience a conversion reaction mechanism, [36] and there are some similar researches to CuS materials for sodium ion storage. [37,38] According to the latest report, nitrogen-doped carbon-coated Cu 9 S 5 bullet-like hollow particles and hierarchical CuS@CoS 2 double-shelled nanoboxes have been prepared by morphology design and nanostructure engineering and both have superior rate capability and long cycle life. [39,40] However, behind the reaction mechanisms there still exist some unclear issues related to the reaction pathways and phase transformation.…”
mentioning
confidence: 99%
“…Fortunately, recent studies have indicated that ether-based electrolytes exhibit high ionic conductivities and offer low resistances to fast kinetics. For example, Xia et al reported the reasonable electrochemical performance delivered by a Ni 3 S 2 /carbon nanotube composite in an ether-based electrolyte . Our research group also reported that the use of an ether-based electrolyte optimized the rate and cycling performances of metal sulfides. , …”
Section: Introductionmentioning
confidence: 69%
“…On the other hand, a facile, scalable, sol−gel route, without any 34 Our research group also reported that the use of an ether-based electrolyte optimized the rate and cycling performances of metal sulfides. 41,42 The present study demonstrates the synthesis of mesoporous Ni 3 S 2 nanoparticles via a facile, scalable sol−gel method. We recorded the electrochemical performance obtained when using mesoporous Ni 3 S 2 as the anode material for SIBs and PIBs; an ether-based electrolyte was employed in the experiments.…”
Section: ■ Introductionmentioning
confidence: 81%
“…CuS, an inexpensive and sustainable material, is regarded as a potential Na‐host anode with high theoretical capacity of 558 mAh g −1 [9,10] . However, analogy to other metal dichalcogenides, CuS suffers from terrible capacity decay and inferior rate capability on account of the intrinsic low conductivity and huge volume change during cycling [11–21] . Considering that the sodium storage processes of CuS includes intercalation and conversion reactions, the volume change mainly occurs during the conversion reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] However, analogy to other metal dichalcogenides, CuS suffers from terrible capacity decay and inferior rate capability on account of the intrinsic low conductivity and huge volume change during cycling. [11][12][13][14][15][16][17][18][19][20][21] Considering that the sodium storage processes of CuS includes intercalation and conversion reactions, the volume change mainly occurs during the conversion reaction. The cycle performance can be significantly improved by controlling the cut-off voltage to prevent the conversion reaction.…”
Section: Introductionmentioning
confidence: 99%